Imaging studies in patients with malignant melanoma in the female genital tract. Issue 5 (1st August 2002) - Takehara, M.; Saito, T.; Mizumoto, H.; Baba, T.; Tanaka, R.; Fujimoto, T.; Adachi, K.; Kudo, R.
Abstract : The purpose of this study was to review magnetic resonance imaging (MRI) and pathologic features of primary malignant melanoma (melanoma) in the female genital tract. We retrospectively evaluated MRI in six women with melanoma of the genital tract. The signal intensity of the tumor on T1-weighted images (WI) was compared with the amount of melanin granules in hematoxylin-eosin stained sections of resected specimen. On T1WI, four melanomas showed a high signal intensity, one intermediate, and one low. The four melanomas with a high signal intensity on T1W1 were rich in melanin granules, while the one intermediate tumor had few granules. The other one was amelanotic. We believe that a high signal on T1WI is characteristic of primary melanotic melanoma of the female genital tract. Our findings suggest that it is strongly influenced by the presence of melanin granules.